Study of Flow and Heat Transfer Characteristics of Lead-Based Liquid Metals in a Turbulent Tube Flow and the Impacts of Roughness - Shen, Yaou; Peng, Shinian; Yan, Mingyu; Zhang, Yu; Deng, Jian; Yu, Hongxing; Huang, Daishun; Li, Zhongchun (Frontiers in Energy Research, 2021)
Lead-based Liquid Metal (LLM) such as Lead-Bismuth Eutectic (LBE) and lead, are the most interesting candidate coolant for fast reactors these years because of their excellent physical properties that can improve safety and reduce cost efficiently. However, the researches on flow and heat transfer characteristics of LLM are limited compared to other liquid metals. Therefore, this work carried out flow and heat transfer experiments in LBE flowing through a circular tube based on Natural Circulation Capability Loop (NCCL) facility. The results show a significantly higher friction factor than that of water flowing in a smooth pipe. And the results of the Nusselt number are lower than literature experimental data carried out in a smooth tube at low Peclet number while higher at high Peclet number. Therefore, theoretical analyzes were performed for LLM flowing in both smooth and rough pipe and the impacts of roughness on heat transfer of LLM were discussed. Theoretical relations for smooth pipe and rough pipe were validated by literature experimental data and the results of NCCL respectively. The results of theoretical relation for smooth pipe fitted literature data well especially for Johnson’s data. The theoretical relation for rough pipe with a relative roughness of 0.004 fitted the NCCL data best. Moreover, it can be learned from the theoretical analysis that the roughness has two competitive impacts on the heat transfer of LLM. It reduces conductive heat transfer while enhancing the convective heat transfer. Because the conductive heat transfer is important for liquid metals even at turbulent flow, small roughness will lead to heating transfer deterioration at low Peclet number or even deteriorated in the whole typical Peclet number range. This discovery has important implications for the thermal-hydraulic design of LLM reactors because corrosion and erosion of LLM will lead to a rough surface after a long time of operating.